창업지원 매니저의 역량 특성이 창업지원단 몰입도와 업무성과에 미치는 영향: 매니저의 자기효능감을 중심으로 - 강혜정(Kang, Hye Jung); 양영석(Yang, Young Seok); 김명숙(Kim, Myung Seuk) (벤처창업연구, 2022)
Korean Government Budget Supports for startups have been spiked and resulted in increasing the number and scaling up Startup Accelerating managers. It have skyrocketed the strong demand for their qualified roles. However, unclear role description and gap between required role and their capability have discouraged startup manager's self-efficacy resulted in declining their full commitment and causing poor role performance. The focus of this research falls on empirical analysis to the effect of startup accelerating manager's capability characteristics on their full commitment and performance to start-up support groups. This research is expected to deliver diverse policy alternatives to build up manager's core competencies to accelerate their self-efficacy leading their full role commitments and finally pushing up policy performance. In addition, this research will found more strong literature review for the following researches in this emerging fields. This research is brought four highlighting results with respect to four research problems. First, it propose proper concept of startup accelerating manager based upon its legal entitlement. Second, it drive required core competencies of manager for successful their accountability. Third, it analyze the unique features of startup accelerating manger's capabilities against business incubation manger. Fourth, it empirically analyze in coming with government startup funding, the effect of self-efficacy including employment status, job environment, etc. on their organizational commitment and job performance. This research reveal the required unique core competencies of manger into founder sourcing ability, project managing ability, startup proving and pivoting ability, consulting ability for successful investment raising. As of this empirical research results, First, manager's ability have positively effect on their job performance, full commitment, and self-efficacy. Second, self-efficacy have a mediating effect on manager's ability, job performance, full commitment. This research derive key policy implication of requiring to build up more accelerating ability, of manager from the basics to advance level by customized and algorithm based traing program. This accelerating ability buildup program will not only surge self-efficacy of manger resulting in making full commitment and better job performance, but also devote to categorizing the unique new feature and position of manger as seed investment and supporter. 2011년 이후, 정부의 창업지원 사업 규모가 급속히 커지며 이를 전담하는 창업지원 매니저의 규모 또한 증가하며 이들에 대한 역할과 역량의 중요성이 커지고 있지만, 창업지원 매니저들에 대한 역할과 역량에 대한 구체적인 개념이나 창업지원 매니저의 요구역량과 보유역량 간의 간극이 커지며 자기효능감이 감소하고 이것이 창업지원단의 몰입도와 업무성과에 부정적인 영향으로 이어지는 문제가 대두되고 있다. 본 연구는 창업지원 매니저의 정의와 창업기업의 성공적인 사업수행을 돕기 위해 요구되는 핵심역량에 따라 매니저가 조직에 몰입할 수 있는 정도와 업무성과에 미치는 영향에 대해 실증분석하는 것에 초점 두며, 이를 통해, 창업지원 매니저의 역량 강화 방안을 제시하여 이들의 자기효능감을 배가하여 창업지원단 업무에 몰입하고 성과를 높이기 위한 정책시사점 도출과 이를 통해 향후 창업지원 매니저 관련 연구에 유용하게 사용될 수 있는 기초자료를 제공을 목적으로 하고 있다. 이를 위해 본연구는 크게 네 가지의 연구를 수행하였고 각각의 연구 결과를 도출하였다. 첫째, 관련 법률적 근거를 가지고 창업지원 매니저에 대한 개념을 제시하였다. 둘째, 창업지원 사업 운영에 있어 창업기업의 성공적인 육성을 위해 매니저에게 요구되는 핵심역량이 무엇인지 도출하였다. 셋째, 창업지원 매니저의 핵심역량에 대한 요인들을 나열하고, 창업보육 매니저들과의 비교를 통해 창업지원 매니저의 역량 차이점을 분석하였다. 넷째, 실증분석을 통해 정부 지원사업의 현실에 따른 창업지원 매니저의 고용 형태, 근무 환경 및 상황 등 창업지원단 조직몰입도와 업무성과 등을 자기효능감을 통해 어떠한 영향을 보여주는지 분석하였다. 본 연구를 통해 창업지원 매니저의 차별적 필요역량은 창업자 발굴역량, 프로젝트 관리역량, 검증·보강역량, 투자유치 컨설팅역량으로 정의하였다. 실증분석 결과 창업지원 매니저역량은 업무성과와 창업지원단 몰입도, 자기효능감에 긍정적인 영향을 미쳤으며, 자기효능감은 창업지원 매니저의 역량과 업무성과, 창업지원단 몰입도 사이에서 매개효과를 나타내는 결과를 얻었다. 기초적인 업무 지식부터 전문적인 지식 습득을 위한 단계적, 맞춤식, 집중 교육 훈련, 창업자들의 빠른 성장을 위한 액셀러레이터 역량 강화 교육 등 이 뒷받침 되어야 하는 점을 시사점으로 제시하고 있다. 이러한 역량 강화 교육 훈련이 이뤄진다면 창업지원 매니저들의 자기효능감은 높아질 것이고 자기효능감이 커질수록 창업지원 매니저는 본인의 역량을 크게 펼칠 수 있고, 이는 조직의 업무성과와 창업지원단 몰입도에 긍정적인 영향을 줄 것이다. 이론적 기여로는 기존 창업보육 매니저의 역량과는 달리 창업자 발굴역량, 프로젝트 관리역량, 검증·보강 역량, 투자유치 컨설팅역량이라는 새로운 창업지원 매니저역량을 도출하였다.